Optimization of Croplands for Efficient and Sustainable Resource Use and Management - Maria Cristina Punay Pammit; Julieta A. Delos Reyes; Antonio Jesus A. Quilloy; Danesto B. Anacio (Journal of Applied Data Sciences, 2026)
The farmers in Ilocos Norte, Philippines, produce vegetable crops during the dry season (November to May). During this time, they face simultaneous climatic and resource challenges, which impact their production decisions and threaten food security. Land use decisions at the farm level require trade-offs due to resource constraints and other inherent factors, thus, informed decision-making is called for. This study determines the optimal cropland allocation where farmers can earn the highest income given their level of existing resources and production objectives during the dry season. Only prime agricultural lands were considered, and it excluded livestock production due to resource limitations and more sophisticated models and analytical software required. Production data from 80 farmers were subjected to optimization through linear programming in Microsoft Excel Solver. Results revealed that the farmers should adjust their current production level and cropland areas during the dry season to further maximize profit. Particularly, the farmer-respondents should devote 2.22-ha croplands to tomato production to earn 208.09 percent higher profit, and another 2.90-ha for purple corn and peanut production to generate 41 percent more profit than their existing crop production system. The study provides scientific evidence that maximum income can be attained if the farmers in the study areas change their existing crop production to the identified best alternative. It also offers information that could be a basis for crafting a decision tool for efficient and sustainable agricultural land use and management in the respective areas. Future studies may consider incorporating price volatility, risk preferences of farmers, crop rotation requirements, and non-linear yield responses. Analysis of wider agricultural lands combined with livestock production may also provide a more comprehensive perspective.